ARtour: Augmented reality-based game to promote agritourism - Garzón, Juan; Acevedo, Juan; Pavón, Juan; Baldiris, Silvia (Lecture Notes in Computer Science, 2020)
Agritourism is an extension of ecotourism, which encourages visitors to experience agricultural life at firsthand. The growing interest in this industry worldwide poses new challenges to the environment. Traditional tourism models have somehow endangered local biodiversity and, consequently, it is necessary to promote new models that include education. Eco-education is commonly conducted through passive learning approaches within educational institutions, which often result in poor student performance in real life. Therefore, it is necessary to generate active methodologies to enrich learning experiences. Augmented Reality holds the power to add multiple benefits to the learning processes. Accordingly, this study introduces “ARtour”. ARtour combines an Augmented Reality experience with on-site experiences to learn about agritourism while encourages tourists to maintain responsible environmental behavior. The project considers two outdoor learning scenarios: aquaponics and subsistence crops. We posit that ARtour will enhance outdoor learning experiences and will be a useful guide to promote agritourism.
Ponencia de la conferencia "5th International Conference on Augmented Reality, Virtual Reality, and Computer Graphics, SALENTO AVR 2018; Otranto; Italy; 24 June 2018 through 27 June 2018"
Keywords: agritourism; augmented reality; eco-education; ecotourism; Scopus(2); JCR; WOS(2)